1994
DOI: 10.1063/1.111253
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoresistance in Fe/Cr superlattices with very thin Fe layers

Abstract: Carefully tailored Fe/Cr epitaxial superlattices with extremely thin Fe layers have been grown on MgO(100) by molecular beam epitaxy. The low-angle x-ray spectra reveal the presence of sharp interfaces down to an Fe layer thickness of a few monolayers. An [Fe(4.5 Å)/Cr(12 Å)]50 superlattice shows a 220% magnetoresistance at 1.5 K, and a saturation field of 110 kOe. A further decrease of the Fe layer thickness produces a drastic decrease in the magnetoresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(53 citation statements)
references
References 19 publications
3
50
0
Order By: Relevance
“…The calculated MR values in the CIP geometry in the ballistic regime [76] were much smaller than the highest experimental values of 115% for Co/Cu multilayers [202] and 220% for Fe/Cr multilayers [203] indicating that some additional scattering mechanism is important. Using a single-band tight-binding model, Asano et al [190] found that, unlike in the CPP case, the CIP MR did depend critically on interface defect scattering.…”
Section: Ballistic Gmrmentioning
confidence: 89%
“…The calculated MR values in the CIP geometry in the ballistic regime [76] were much smaller than the highest experimental values of 115% for Co/Cu multilayers [202] and 220% for Fe/Cr multilayers [203] indicating that some additional scattering mechanism is important. Using a single-band tight-binding model, Asano et al [190] found that, unlike in the CPP case, the CIP MR did depend critically on interface defect scattering.…”
Section: Ballistic Gmrmentioning
confidence: 89%
“…For the present example the relatively low value for p Τ and the significant value for p J, is again favorable for a large GMR [51]. Therefore for Fe/Cr, being todays record GMR system [48], this simple procedure works out quite well. However, this appears to be fortuitous and not generally applicable.…”
Section: T O T H E O R I G I N a L H Y P O T H E S I S O Fsmentioning
confidence: 95%
“…Values of 0.1% for V and Mo based multilayers are found whereas the record value today is 220% for the Fe/Cr system [48]. Closer examination of the various multilayer systems which have been studied so far, learns that for the magnitude of the GMR effect the material combination is crucial.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…A 30 nm thick Cr(0 0 1) buffer layer grown at 450 • C and subsequently annealed at 750 • C is necessary for a good epitaxial growth of the Co/Cr/Fe spin valve structure. Cr exhibits a so-called 45 • -epitaxy on MgO(0 0 1) with the [1 0 0] crystallographic axes of both materials being aligned at an angle of 45 • to each other [9].…”
Section: Sample Preparationmentioning
confidence: 99%